Evaluation of new stream ciphers for multimedia in resource-constrained devices - Caballar, Rina Diane F. (2008)
The widespread use of multimedia applications such as videoconferencing, telemedicine, and others is proof of the significant role multimedia plays in society. The prevalence of multimedia has led to its rapid and uncontrollable distribution through vulnerable channels such as the Internet. Thus, a need for multimedia security arises. In this thesis, stream cipher encryption of multimedia content in resource-constrained devices was developed as a fast and secure method of protecting multimedia content. Stream ciphers enable fast computations and have small memory requirements and can therefore take advantage of the processing power and limited storage capabilities of resource-constrained devices. Specifically, selected stream ciphers from the eSTREAM project were implemented on a smart card and were used to encrypt JPEG and PNG still images. Our results indicate that stream cipher encryption in smart cards is fast for small-sized images. To further speed up the encryption process, a generic selective encryption scheme such as the Video Encryption Algorithm (VEA) was integrated with stream cipher encryption in smart cards. Our results confirm the reduction in encryption time by more than half using VEA. For large-sized images, the accelerated remotely keyed (ARK) encryption schemes was employed. In this scheme, part of the encryption is done by the smart card and a bulk of the encryption is performed on the host. Encryption using the ARK encryption scheme is fast and is therefore suitable for encrypting multimedia content.